Financial Decisions and Firm Value: The Moderating Role of Good Corporate Governance and Environmental Disclosure - PRAMARTHA , I Made Aditya; PUTRA, Gede Sanjaya Adi; RAI, Ida Ayu Putu Liony Natasha (PT Keberlanjutan Strategis Indonesia, 2025)
This research aims to examine the effect of investment decisions, funding decisions, and dividend policy on firm value by including good corporate governance and environmental disclosure as moderating variables. This research was conducted on 47 banking sub-sector companies listed on the Indonesia Stock Exchange in 2023, to provide an empirical picture of the dynamics of financial decision-making and its implications for market valuation. The approach used is quantitative research with data analysis techniques, Moderated Regression Analysis, to test nine research hypotheses, based on secondary data obtained from the company's annual report. The results showed that investment decisions and dividend policy had a positive effect on firm value, while funding decisions had no significant effect. Meanwhile, institutional ownership and environmental disclosure are not proven to moderate the relationship between the three financial decisions and firm value. These findings indicate that investment decisions and dividend policies are important signals for the market, while the moderating role of good corporate governance and environmental disclosure is not optimal in the context of the banking industry. This research is expected to enrich empirical studies related to signal theory and provide input for company management and stakeholders in formulating financial strategies and sustainability policies that support the increase in firm value.